The relationship between weight and length of male broodstock with gamete production in the narrow-clawed crayfish Pontastacus leptodactylus (Eschscholtz, 1823) - Farhadi, Ardavan; Harlioglu, Muzaffer Mustafa; Harlioglu, Ayse Gul (Wiley, 2019)
[Abstract Not Available]
Keywords: decapod; sexual maturity; spermatophore; spermatozoon